Differences in Uptake of 18F-FDG and 11C-Choline in a Case of Acute Myeloid Leukemia. (October 2016) - Qin, Chunxia; Wu, Zhijian; Li, Ji; Sun, Xun; Lan, Xiaoli
Abstract : Abstract: A 26-year-old man had unilateral facial numbness. A brain MRI suggested possible brain metastases. 18 F-FDG and 11 C-choline PET/CT revealed multiple sites of abnormal activity in the body. However, 11 C-choline PET/CT was more impressive than FDG PET/CT. Especially, the brain lesions revealed by MRI had only elevated 11 C-choline uptake but had FDG uptake levels similar to adjacent brain. Acute myeloid leukemia was diagnosed after bone marrow biopsy.